2018
DOI: 10.1016/j.powtec.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation on the effect of particle size into the flowability of fly ash

Abstract: In this paper, physical properties and flow properties of fly ash collected from seven fields of Electro-Static precipitator (ESP) hoppers of a coal fired thermal power plant have been investigated by using Powder Flow Tester operating based on Jenike's methodology. It was experimentally observed that the fly ash from different ESP hoppers have different flow properties. Various powder flow properties, such as cohesion, unconfined yield strength, angle of internal friction and wall friction angle were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Similar conclusions for black soybean powders, where fine fractions were reported as cohesive, were made by [18]. Rohilla [19] concluded that there exists a particular particle size after which intermolecular forces become larger than weight forces, which triggered a decrease on flowability of fly ash samples.…”
Section: Introductionsupporting
confidence: 66%
“…Similar conclusions for black soybean powders, where fine fractions were reported as cohesive, were made by [18]. Rohilla [19] concluded that there exists a particular particle size after which intermolecular forces become larger than weight forces, which triggered a decrease on flowability of fly ash samples.…”
Section: Introductionsupporting
confidence: 66%
“…The wall friction angles decrease with increasing wall normal stress, which is in accordance with various published data [36][37][38][39]. However, this effect was not equally pronounced for all wall materials and powder particle sizes.…”
Section: Wall Friction Anglessupporting
confidence: 91%
“…Distinguishing foreground pixels from the background pixels has been used to enhance visual perception of images [13][14][15]. One of the common techniques used to identify morphological maps [16] and image color intensity and is the threshold segmentation. The technique offers a simplicity in calculation and speed in operation [17].…”
Section: Image Segmentation and Thresholdingmentioning
confidence: 99%